(untitled) (Journal of the College of Basic Education, 2023)
The research aims to identify the effect of using the Deniz model on the achievement and retention of first-grade intermediate students in mathematics.The research sample consisted of (30) students in Al-Wafa Secondary School for Girls affiliated to the General Directorate of Education of Baghdad / Al-Rusafa II, as the researcher distributed the first-grade students randomly into two divisions, and the number of students in each division was (15) students, and division (A) represented the experimental group that was studied using Dean’s model Division (B) represented the control group that was taught using the usual teaching method. The researcher used the experimental design (the experimental group and the control group) and the partial control.The two research groups were rewarded in terms of (chronological age and half-year grades). The researcher prepared the teaching plans and the final achievement test. This test was characterized by honesty and stability. The coefficient of difficulty, ease, and discrimination was found for the optional paragraphs. Student retention of sports information.The researcher used the (T) test to compare the results.The results resulted in:There is a statistically significant difference at the level of significance (0.05) between the mean scores of achievement and retention of female students in the experimental group and the average scores of achievement and retention of female students in the control group, in favor of the experimental group.In light of the results of the research, the researcher concluded that there is a positive effect of using the Deans model on the collection and retention of mathematics for the first intermediate grade. The researcher recommended a number of recommendations and suggestions.